PENYULUHAN HUKUM TENTANG PROBLEMATIKA PERKAWINAN DIBAWAH UMUR DI SMKN 2 TANAH PUTIH KABUPATEN ROKAN HILIR - Apriani, Desi; Kurniasih, Esy; Febrian, Rojja; Milandry, Anggraini Dwi (Jurnal Abdi Masyarakat, 2023)
The purpose of this community service is to provide socialization, understanding, and provision of knowledge and actual information related to the problems of underage marriage both in theoretical and practical terms. The main problem faced by partners is that partner communities (both educators and students) donâ€™t really understand the problems of underage marriage, because the information obtained are still makes them confused, besides schools are one of the effective and closest forums to the community to be able to "create or bring outâ€ humans with certain characters in social and national life. The solution offered in this community service are first provide legal counseling on the basis of marriage law arrangements in Indonesia, especially those related to the age limit for performing a marriage. Second, providing information related to knowledge about underage marriage in Islamic concepts and third explaining general knowledge related to technical problems in the implementation of underage marriage that have a positive and negative impact on the life of a couple, both personally and in social life. The method of implementing community service activities is carried out in several stages. The core stage of this activity is to provide legal counseling by presenting material and ending with a discussion session. The result of this activity is that, with the implementation of community service activities, in addition to the participants being very enthusiastic about participating in the activity, partner communities (both educators and students) have gained actual insights and additional knowledge of marriage law in force in Indonesia.